Social Aspects of New Technologies - the CCTV and Biometric (Framing Privacy and Data Protection) in the Case of Poland - Wysokinska, Zofia; Dziuba, Radosław (Comparative Economic Research. Central and Eastern Europe, 2012)
The purpose of this paper is to review the institution responsible for the protection of personal data within the European Union and national example - Polish as a country representing the new Member States. The analysis of institutional system - providing legal security of communication and information institutions, companies and citizens against the dangers arising from the ongoing development of innovative new technologies in the European Union and Poland. This article is an attempt to analyze the possibility of using security systems and Biometry CTTV in Poland in terms of legislation. The results of the analysis indicate that, in terms of institutions Poland did not do badly in relation to the risks arising from the implementation of technology. The situation is not as good when it comes to the awareness of citizens and small businesses. This requires that facilitate greater access to free security software companies from data leakage or uncontrolled cyber-terrorist attacks. With regard to the use of security systems, CCTV and biometrics, Poland in legal terms is still early in the process of adapting to EU Directive. The continuous development of technology should force the legislature to establish clear standards and regulations for the application of CCTV technology and biometrics, as it is of great importance in ensuring the fundamental rights and freedoms of every citizen of the Polish Republic.